Mesenteric Mesothelial Cyst a Relatively Rare Complication of Peritoneal Dialysis and Intra-Abdominal Surgical Sequel, Case Presentation (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Internal Medicine; Case Report